2014
DOI: 10.4236/ijcm.2014.51008
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Year Review of Gynaecological Oncology Patients Managed by a Fast Track Surgery Program

Abstract: Introduction: The aim of this study is to provide a comprehensive 5-year audit of patients undergoing laparotomy for suspected or confirmed gynaecological malignancy to document the frequency and incidence of adverse events and to investigate factors associated with shorter length of stay and readmission to hospital. Methods: A 5-year surgical audit of the period commencing 2008 and concluding 2012. All patients undergoing laparotomy were included in the audit without exclusions. Approval was granted by the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…It has already been demonstrated that ERAS protocols are safe and effective pathways in the management of patients with gynaecological malignancy 2–4,9–11 . However, the findings of this study also report that most patients find it not just an acceptable option but highly satisfying, corroborating the findings of similar studies 7,8 …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It has already been demonstrated that ERAS protocols are safe and effective pathways in the management of patients with gynaecological malignancy 2–4,9–11 . However, the findings of this study also report that most patients find it not just an acceptable option but highly satisfying, corroborating the findings of similar studies 7,8 …”
Section: Discussionsupporting
confidence: 85%
“…The gynaecological oncology department in our unit has successfully adopted the ERAS pathway for over ten years, enabling a shorter length of stay with comparable complication and readmission rates to the standard post‐operative protocol 2–4 . While there is evidence that ERAS pathways are associated with comparable patient satisfaction to conventional pathways in other fields in surgery, 5,6 such data are still lacking in the field of gynaecological oncology due to low power and recruitment rates in the existing literature 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…To give some indication of the generalizability of our results, we compared the characteristics of women who participated in this study to gynecological oncology patients included in a recent 5-year audit of the gynecological cancer clinic at Royal Prince Alfred Hospital, Sydney. 47 We found that they had a fairly similar mean age (57.5 vs 54.8 years, respectively) and mean BMI (27.1 vs 28.1 kg/m 2 , respectively). Both hospitals in this study were located in inner-city Sydney.…”
Section: Discussionmentioning
confidence: 55%